Nightshade (Solanum nigrum), an intermediate host between tomato and cucurbits of Tomato leaf curl New Delhi virus - Mohammad Ansar (Firenze University Press, 2021)
Geminiviruses infect many crop plants, and are limiting factors for vegetable crop production. Begomoviruses (Geminiviridae) cause typical symptoms of leaf curling and puckering in nightshade (Solanum nigrum), a seasonal weed in Bihar, India. To investigate if nightshade was an intermediate host for begomovirus, virus DNA was extracted and characterized. The DNA-A of the virus yielded 2737 nt and DNA-B yielded 2706 nt. The intergenic region (IR) showed a conserved nonanucleotide sequence that potentially forms a stem-loop structure. The genomic sequence of DNA-A shared 94% identity with that of Tomato leaf curl New Delhi virus (ToLCNDV)-ivy gourd isolate. However, the sequence of DNA-B showed 95% identity with a bitter gourd isolate. PCR-based detection revealed the presence ToLCNDV in bottle gourd, pumpkin, sponge gourd, and bitter gourd. The IR sequences of the viruses isolated from these cucurbits and tomato were 100% identical. Whitefly-mediated transmission of the virus to cucurbits and tomato from nightshade was also demonstrated. These results indicate that nightshade may act as reservoir of ToLCNDV, and is involved in developing epidemics in cucurbit species. The strain of ToLCNDV has probably adapted from solanaceous to cucurbitaceous hosts. This is the ﬁrst report of ToLCNDV infecting nightshade in India, highlighting this virus as a possible cause of disease epidemics in economically important cucurbits.